La producción del orden social y la definición del delincuente político en Colombia a finales del siglo XIX (1876-1885) - Alzate G., Adrián (Sociedad y Economía, 2007)
The follow pages try to offer an approach of the political debate about the political criminalthat developed in Colombian at the end of the nineteenth century. This debate was related withconílict between two political fraction that were looking for ensure a social order anddevelopment in the country.